Menelaah Kitab Syarḥ Al-Arba‘īn An-Nawawiyyah Karya al-‘Usaimin: Sebuah Kajian Pemahaman Islam Kontemporer - Adli, Muhammad; Hakim, Putri Rahmah Nur; Abdullah, Irwan (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
This study explores the hadith commentary (sharḥ) in Al-Arba‘īn an-Nawawiyyah by Muhammad ibn Ṣāliḥ al-‘Usaimin. It focuses on assessing the depth and methodology of al-‘Usaimin’s interpretation of the forty hadiths compiled by Imam al-Nawawī. The objective is to examine how al-‘Usaimin presents his commentary and how his approach contributes to a more nuanced understanding of Islamic teachings within a contemporary framework. This research adopts a qualitative library research design. The primary data source is al-‘Usaimin’s Syarḥ al-Arba‘īn an-Nawawiyyah, while secondary sources include relevant books, academic journals, and other scholarly works. Data were collected through various references, including printed and digital materials. The analysis applies discourse analysis, involving the systematic examination and interpretation of texts from both primary and secondary sources. The findings indicate that al-‘Usaimin’s commentary is marked by a strong integration of Qur’anic verses to reinforce the meanings of the hadiths. His adherence to the structure and order established by al-Nawawi reflects a methodological consistency, while his inclusion of supplementary hadiths enriches the explanatory depth. Overall, al-‘Usaimin’s work demonstrates a thoughtful and systematic effort to contextualize prophetic traditions for modern readers, offering a comprehensive and spiritually grounded interpretation.